Mindfulness‐based stress reduction and cognitive function among breast cancer survivors: A randomized controlled trial. Issue 13 (6th April 2022) - Duval, Alicia; Davis, Christopher G.; Khoo, Eve‐Ling; Romanow, Heather; Shergill, Yaadwinder; Rice, Danielle; Smith, Andra M.; Poulin, Patricia A.; Collins, Barbara
Abstract : Background: Breast cancer (BC) survivors frequently report changes in cognition after chemotherapy. Mindfulness may benefit survivors by mitigating cancer‐related cognitive impairment. As part of a larger study investigating the effects of mindfulness‐based stress reduction (MBSR) for BC survivors living with neuropathic pain, the authors assessed whether MBSR would have an effect on cognitive outcomes. Methods: Participants were randomized to an MBSR intervention group (n = 30) or a waitlist control group (n = 30). Cognitive assessments were administered at 3 time points: at baseline, 2 weeks, and 3 months post‐MBSR in the intervention group and at equivalent time intervals for the control group. Multilevel models were used to assess whether MBSR significantly improved task performance at each time point. Results: MBSR participants showed a significantly greater reduction in prospective and retrospective memory failures at 2 weeks postintervention. No effects of MBSR were noted for objective assessments. Conclusions: These results suggest that MBSR training reduces subjective (but not objective) memory‐related impairments in BC survivors who receive treatment with chemotherapy. This study provides insight into a noninvasive intervention to ameliorate memory difficulties in BC survivors. Abstract : Breast cancer survivors often reported cognitive impairments after chemotherapy treatments. This study illuminated a noninvasive intervention to alleviate the pervasive symptoms of cancer‐related cognitive impairment that was mindfulness‐based stress reduction.